Frequency of therapy-relevant staging shifts in colorectal cancer through the introduction of pN1c in the 7th TNM edition - Winterfeld, Moritz von; Herpel, Esther; Schirmacher, Peter; Bläker, Hendrik (European journal of cancer, 2014)
Background - pN1c is a novel N-category introduced for colorectal cancer (CRC) in current TNM (Tumour, Node, Metastasis) classification. It represents cancers displaying tumour deposits (TDs) in the fat but no involvement of lymph nodes. pN1c is integrated into the UICC (International Union Against Cancer) staging system and shifts previous stage II cancers (6th edition) to stage III. We investigated the frequency of upstaging and TD prognostic significance. - Methods - 414 CRCs, consecutively collected during a population-based epidemiological study, TNM classified and UICC staged according to the 6th TNM edition were reinvestigated for TD presence. The association with survival was investigated after a median follow-up time of 5years in multivariate analyses among nodal negative and positive cases. - Results - TDs were found in 103 (24.9%) cancers and were strongly associated with T-, N- and M-stages (p<0.0001, each). Upstaging of previous stage II cancers by the presence of TDs (pN1c) was found in six of 140 cases (4.3% of stage II, 1.4% of all tumours). For stage III CRC, strongly reduced overall, CRC-specific and recurrence-free survival were observed with the presence of TDs (hazard ratios (HR) 2.29, 95% confidence interval 1.27-4.10, HR 2.51, 1.27-4.98, and HR 2.43, 1.32-4.48, respectively). - Conclusions - Upstaging of CRCs through the introduction of pN1c occurs in less than 5% of previous stage II and less than 2% of all cancers. Given the biologic relevance of TDs, integration into the UICC staging relevant N-category is justified. The high prognostic impact of TDs, however, is not reflected in nodal positive cancers in both the TNM and UICC staging systems.
Gesehen am 22.09.2020